Postural stability measures as diagnostic tools for chronic ankle instability: a comprehensive assessment - Makan Piri; Kazem Malmir; Khadijeh Otadi; Azadeh Shadmehr (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Chronic ankle instability (CAI) is characterized by recurrent sprains and persistent symptoms, which impair postural control. This study evaluates the diagnostic utility of various linear and nonlinear postural stability measures in distinguishing individuals with CAI from healthy controls. Methods Postural stability was assessed in 24 participants (12 with CAI and 12 healthy controls) using a force platform under four conditions: hard surface with eyes open, hard surface with eyes closed, soft surface with eyes open, and soft surface with eyes closed. Linear measures of center of pressure (COP) included range in the anteroposterior (Rfa) and mediolateral (Rsw) directions, mean velocity (MV), and sway area. Nonlinear measures included approximate entropy (ApEn), the largest Lyapunov exponent, and correlation dimension (CD) with its standard deviation. Diagnostic accuracy was evaluated using receiver operating characteristic (ROC) analysis to determine cutoff scores, allowing effective differentiation between CAI and healthy participants. Result AI individuals exhibited increased mediolateral COP sway and higher mean velocity on hard surfaces with both eyes open and closed. On soft surfaces with eyes closed, they showed significant deficits in sway area and mean velocity, reflecting challenges in postural control. ROC analysis revealed that certain linear and nonlinear measures showed strong diagnostic accuracy in distinguishing individuals with CAI from healthy controls. Nonlinear analysis revealed elevated ApEn and reduced CD in CAI participants, indicating greater postural irregularity and reduced dynamic stability. On a hard surface with eyes open both Rsw (cutoff: 1.18 cm, OR: 4.55) and ApEn (cutoff: 0.07, OR: 4.0) were particularly strong diagnostic indicators. Conclusion Linear and nonlinear postural stability measures effectively differentiate individuals with CAI from healthy controls. Key metrics, including Rsw, MV, ApEn, and CD, offer strong diagnostic value for early detection and personalized rehabilitation. Incorporating these measures into clinical practice may improve CAI management and patient outcomes. Ethical code IR.TUMS.FNM.REC.1400.236. March 14, 2022.